Перспективи розвитку технології мобільного зв’язку 4G - Сабурова, С. А.; Кадацкая, О. И.; Козубенко, В. С. (ХНУРЕ, 2019)
The organization of subscriber access to multiservice 4G-based networks are relevant in the light of providing subscribers with high-speed latest technology and new services. The main feture of the current stage of development of cellular communication systems is the transition to fourth-generation systems. The transition to LTE-Аdvanced (4G) networks allows us to qualitatively change the current situation in the field of mobile communications. This is due primarily to the fact that LTE-Аdvanced networks can provide customers with a wide range of new services that can significantly increase the revenues of operators, and for manufacturers - sales of network equipment and telephones.
Keywords: 4G; LTE-Advanced; LTE; LTE-А